Supplementation of Feed Grade Sodium Bisulfate in Broiler Diets Improves Feed Efficiency - Ruiz-Feria, C.A.; Larrison, E.; Davis, M.; Farnell, M.; Carey, J.; Grimes, J.L.; Pitts, J. (International Journal of Poultry Science, 2011)
The effects of Sodium Bisulfate (SB) supplementation on growth, intestinal integrity, blood gas chemistry and litter microbiology of broiler chickens were evaluated. Birds were fed a corn-soybean meal diet meeting all of the NRC (1994) requirements. In Exp. 1 birds were fed diets supplemented with 0 (control diet, CTL), 0.25, 0.5, or 0.75% (w/w) of feed-grade SB (SB25, SB50 and SB75, respectively); in Exp. 2 and 3 only the CTL, SB25 and SB75 diets were evaluated. In Exp. 4 the chicks (n = 920) were placed in 20 pens and fed the CTL diet, or the SB25 diet offered during the first 21, 35, or 49 d (21D, 35D and 49D, respectively); the CTL diet was offered until the end of experiment (d 49) for treatments 21D and 35D. The data was analyzed as a two way ANOVA (diet and gender as main effects). In Exp. 1 birds fed diets with SB had lower FC than birds fed the CTL diet, but BW was not different among treatments. In Exp. 2 females fed the SB25 diet were heavier (p<0.05) at d 21 than females fed the CTL or the SB75 diet; the FC was similar among groups. In Exp. 3 chickens fed the SB25 or SB75 diets were consistently heavier and had a lower FC (p<0.05) than birds fed the CTL diet. In Exp. 4 birds fed the SB25 diet had lower BW than birds fed the CTL diet; however birds in the 35D or 49D treatments had a better FC than birds fed the CTL diet. The litter of birds fed the SB25 diet had lower levels of Salmonella at wk 4 and 6 in Experiment 3 and at wk 4 in Exp. 4. Neither the duodenum villus height nor the blood gas composition was affected by the dietary treatments. Our results show that SB supplementation improves productive performance and reduces the environmental levels of Salmonella, with variable efficacy, perhaps due to seasonal conditions.